CARMEN, a human super enhancer-associated long noncoding RNA controlling cardiac specification, differentiation and homeostasis. (December 2015) - Ounzain, Samir; Micheletti, Rudi; Arnan, Carme; Plaisance, Isabelle; Cecchi, Dario; Schroen, Blanche; Reverter, Ferran; Alexanian, Michael; Gonzales, Christine; Ng, Shi Yan; Bussotti, Giovanni; Pezzuto, Iole; et al.
Abstract: Long noncoding RNAs (lncRNAs) are emerging as important regulators of developmental pathways. However, their roles in human cardiac precursor cell (CPC) remain unexplored. To characterize the long noncoding transcriptome during human CPC cardiac differentiation, we profiled the lncRNA transcriptome in CPCs isolated from the human fetal heart and identified 570 lncRNAs that were modulated during cardiac differentiation. Many of these were associated with active cardiac enhancer and super enhancers (SE) with their expression being correlated with proximal cardiac genes. One of the most upregulated lncRNAs was a SE-associated lncRNA that was named CARMEN, (CAR)diac (M)esoderm (E)nhancer-associated (N)oncoding RNA. CARMEN exhibits RNA-dependent enhancing activity and is upstream of the cardiac mesoderm-specifying gene regulatory network. Interestingly, CARMEN interacts with SUZ12 and EZH2, two components of the polycomb repressive complex 2 (PRC2). We demonstrate that CARMEN knockdown inhibits cardiac specification and differentiation in cardiac precursor cells independently of MIR-143 and -145 expression, two microRNAs located proximal to the enhancer sequences. Importantly, CARMEN expression was activated during pathological remodeling in the mouse and human hearts, and was necessary for maintaining cardiac identity in differentiated cardiomyocytes. This study demonstrates therefore that CARMEN is a crucial regulator of cardiac cell differentiation and homeostasis. Highlights: LncRNAs are differentially expressed during cardiac precursor cell differentiation. LncRNAs are associated with cardiac specific enhancer and super-enhancers (SE). Identified CARMEN as a SE-associated lncRNA necessary for cardiac differentiation CARMEN expression is activated during pathological cardiac remodeling.